Ceza hukukunda zamanaşımı - Alşahin, Mehmet Emin (My University, 2010)
ÖZET “Geç gelen adalet, adalet değildir” deyişinin bir uzantısı olan zamanaşımı kurumu, ülkemizde özellikle ceza davalarında büyük önem arz etmektedir. Zira mahkemelerde yeterli personelin bulunmaması, iş yükünün fazlalığı, usuli bir takım yanlışlıklar nedeniyle davalar zamanaşımına uğramaktadır. Zamanaşımı, kanunda öngörülen belli sürelerin geçmesi ile devletin cezalandırma yetkisini ortadan kaldırmaktadır. Belli bir sürenin geçmesi ile suç unutulduğu için, zamanaşımı fiilin cezalandırılmasını ve tedbirlere hükmedilmesini engeller. 5237 sayılı TCK’da zamanaşımı, dava ve ceza zamanaşımı olmak üzere iki şekilde düzenlenmiştir. Dava zamanaşımı, kanunda öngörülen sürelerin geçmesi ile birlikte kamu davasının açılması veya açılmış olan davaya devam edilmesine engel olmakta; ceza zamanaşımı ise, kanunda öngörülen sürelerin geçmesi ile kesinleşmiş olan mahkûmiyet hükmünün infazına başlanmasını engellemektedir. 5237 sayılı TCK’nun 66 ncı maddesinde yer alan dava zamanaşımı sürelerine bakıldığında, 765 sayılı TCK’ya göre daha uzun sürelerin öngörüldüğü anlaşılmaktadır. Zamanaşımı, şüpheli, sanık veya hükümlü için kanun tarafından tanınmış bir haktır. Zamanaşımı niteliği gereği re’sen göz önünde bulundurulmalıdır. Bu itibarla ilgililerin zamanaşımının tatbiki konusunda talepte bulunmalarının veya bu haktan vazgeçmelerinin bir önemi yoktur.

ÖZET The statute of limitations which is a prolongation of the statement “Delayed justice is not justice.” holds key especially for criminal cases in our country. A lot of cases are barred by the statute of limitations due to shortage of personnel, caseload and procedural errors. By running of certain periods of time which are prescribed by law, statute of limitations remove the government’s authority of penalization. Since the offense is forgotten due to effluxion of a particular amount of time, the statute of limitations interferes with the penalization of the criminal offense and infliction of temporary injunctions. The statute of limitations is arranged under two titles as the limitation of actions and the limitation of penalization in Turkish Criminal Code of number 5237. The limitation of actions blocks the opening of a criminal case or the progression of an opened criminal case as a result of running of certain periods of time prescribed by law, as well as the limitation of penalization disables judicial sentence from being executed as a result of running of certain periods of time prescribed by law. When the time periods for limitation of actions in Article 66 of Turkish Criminal Code of number 5237 are examined, the longer terms prescribed by law are to be realized compare to the regulations in previous Turkish Criminal Code of number 765. Limitation is a right given by law for the suspect, accused and convicted. The statute of limitation must be taken into consideration sua sponte by its very nature. For this reason, the persons concerned requesting the practise of limitation or releasing the right of limitation is of no importance.
Keywords: Ceza Hukuku; Hukuk; Kamu Hukuku